Perspektif Feminisme Standpoint Pada Perjuangan Perempuan Palestina Terhadap Sikap Diskriminatif Tentara Israel Dalam Konflik Israel-Palestina - Yovanka Ayunita Deborah Lasut; Mohamad Rosyidin; Marten Hanura (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
Awareness of women's rights is very low in Palestine. Most of the Palestinian women have lost their basic rights because of the ongoing Israeli-Palestinian conflict. Israel's security policies have harmed women including imposing restrictions on free movement, demolition of houses, and carrying out torture during interrogation. this issue creates a feeling of insecurity for Palestinian women. This encourages Palestinian women to carry out resistance movements. Therefore, the author's research aims to find out how the struggle of Palestinian women against the discriminatory actions of the Israeli army by analyzing using standpoint feminism theory and the concept of gender which is in line with women's rights. Based on the results of this study, the authors found a discussion that revealed that the Palestinian women's movement is a response to all forms of discrimination committed against Palestinian women by Israeli soldiers with the aim of liberating Palestine from Israeli rule so that they can regain their rights that have been deprived of them.